Gender Role of Household Decision Making (A case study Namobudda Kavre) - Acharya, Suresh (Kutumbha vani, 2024)
Gender roles in household decision making refer to the traditional division of responsibilities and decision-making power between men and women within a family or household. Historically, many societies have adhered to traditional gender roles, where men are often considered the primary decision-makers, particularly in matters related to finances and major family decisions. Women, on the other hand, have often been assigned the roles of managing the household, taking care of children, and dealing with domestic matters. However, it's important to recognize that gender roles are not fixed and vary significantly across cultures, regions, and individual households. Moreover, over time, many societies have witnessed a shift in traditional gender roles, with more emphasis on gender equality and shared decision making. The main purpose of this research was to understand the perception of people regarding the evolvement of gender roles in any household decision making. A Descriptive Cross Sectional study method was used. Altogether, 40 respondents were selected through purposive sampling method, questionnaires, Face to face interview, Informal focused group discussion; Key informant interview method was used using Structured Questionnaire to collect data from respondents. Data analysis was done through MS Excel. It is revealed from the research Gender roles in household decision making refer to the traditional division of responsibilities and decision-making power between men and women within a family or household. Historically, many societies have adhered to traditional gender roles, where men are often considered the primary decision-makers, particularly in matters related to finances and major family decisions. Women, on the other hand, have often been assigned the roles of managing the household, taking care of children, and dealing with domestic matters. However, it's important to recognize that gender roles are not fixed and vary significantly across cultures, regions, and individual households. Moreover, over time, many societies have witnessed a shift in traditional gender roles, with more emphasis on gender equality and shared decision making